New Reconfigurable Transmitarray Unit Cell Design at Ku-Band Using PIN Diodes (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Beam reconfigurable Transmitarray antennas require the unit cell phase variation capability. This paper presents a new reconfigurable Transmitarray unit cell design using PIN diodes at the Ku-band. The unit cell is comprised of three layers having four PIN diodes used in every unit cell layer. This results in phase controlling by switching the PIN diodes on every layer individually. The unit cell s-parametric analysis shows a high transmission coefficient magnitude (> -3.6dB) at a design frequency of 12.5GHz and maximum wide impedance bandwidth (17.5%). Four different switching states configurations are used, which result in phase variations over the range of 150.5 degrees. The transmission coefficient magnitude remains high for all four switching states. The proposed reconfigurable unit cell can be used in designing beam switched Transmitarray antennas for satellite communications and beam steering applications.